2020
DOI: 10.18632/aging.202194
|View full text |Cite
|
Sign up to set email alerts
|

Coicis semen protects against focal cerebral ischemia-reperfusion injury by inhibiting oxidative stress and promoting angiogenesis via the TGFβ/ALK1/Smad1/5 signaling pathway

Abstract: Background: Ischemic stroke is a devastating disease that causes long-term disability. However, its pathogenesis is unclear, and treatments for ischemic stroke are limited. Recent studies indicate that oxidative stress is involved in the pathological progression of ischemic stroke and that angiogenesis participates in recovery from ischemic stroke. Furthermore, previous studies have shown that Coicis Semen has antioxidative and anti-inflammatory effects in a variety of diseases. In the present study, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 53 publications
1
39
0
1
Order By: Relevance
“…The new research demonstrated that taraxasterol has the in vitro anti-inflammatory effect, which is one of the chief active components isolated from Herba Taraxaci Mongolici [ 21 ]. Flos Carthami [ 22 ] and Semen Coicis [ 23 ] are perhaps connected to its antioxidation and anti-inflammatory properties. Semen Persicae, Poria, Radix Glycyrrhizae, and Radix Salviae Miltiorrhizae are related to immune index, for instance, IgM, IgA, and IgG.…”
Section: Discussionmentioning
confidence: 99%
“…The new research demonstrated that taraxasterol has the in vitro anti-inflammatory effect, which is one of the chief active components isolated from Herba Taraxaci Mongolici [ 21 ]. Flos Carthami [ 22 ] and Semen Coicis [ 23 ] are perhaps connected to its antioxidation and anti-inflammatory properties. Semen Persicae, Poria, Radix Glycyrrhizae, and Radix Salviae Miltiorrhizae are related to immune index, for instance, IgM, IgA, and IgG.…”
Section: Discussionmentioning
confidence: 99%
“…MDA is one of the end products of the lipid peroxidation reaction caused by oxygen free radicals, which can cause degeneration and damage of cell membranes and reduce the fluidity and permeability of cell membranes. The content of MDA indirectly reflects the degree of tissue damage by free radicals [ 23 ]. Both SOD and GSH-Px are antioxidant enzymes in the body.…”
Section: Discussionmentioning
confidence: 99%
“…CAT can disproportionate and decompose oxygen free radicals to produce H 2 O 2 through SOD disproportionation to avoid cytotoxicity ( Wattanathorn et al, 2020 ). MDA is the final product of oxygen-derived free radicals and lipid peroxidation and an important sign of oxidative damage ( Du et al, 2020 ). To assess the level of oxidative stress, we found that SOD, GSH-Px, CAT activities were reduced, while MDA level was increased in the serum and cerebral ischemic region after IS (after 24 h); while this effect was reversed by TFCJ.…”
Section: Discussionmentioning
confidence: 99%